Instrument Of Singing Performance Assesment With The Android Based Inventor App (Jurnal Seni Musik, 2020)
Singing performance assessment still subjectively graded by jury, teacher, or committee. To understand assessment aspects in singing, the information was obtained from two experts one from junior high school 24 Semarang and the other a musician, Purwacaka, who has Musical School Purwacaka in Indonesia. This research aimed to produce singing performance assessment application with App Inventor 2 (AI2) that managed by Massachussetts Institute of Technology (MIT). AI2 is a cloud-based saving that could be accessed from internet browser. ADDIE development model with 5 steps, which are: Analysis, Design, Develop, Implementation, and evaluate. Indicators in this research were practicality, attractiveness, accuracy, and quickness in assess. Data collection for needs analysis taken qualitatively by interview and documentation. The singing assessment application consist of four assessment criteria, there are: technique, expression, song interpretation, and demonstration that form 18 items. This application has been tested by three experts by result: attractive, accurate score, and faster score calculation. The improvement for this application was score that could only be seen one by one later should be showed entirely and could be printed Keywords: Performance Assesment, Singing, Based on Android, ADDIE